Surgical Management Of Recurrent Genital Prolapse In The Cows By Button Fixation And Vaginopexy - Desai, B.D.; Tank, P.H.; Vadaliya , J.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present clinical study was carried out in Saurastra region of Gujarat. Total 12 animals affected with various kinds of genital prolapses were studied. The animals were divided into two groups of 6 each. Animals affected with genital prolapses treated by vaginopexy and button fixation in group 1 and 2, respectively. Both the technique was done by administering epidural anaesthesia in animals. Half circled “U” shaped needle was used in vaginopexy technique and straight needle was used for button fixation technique. A marked pus formation was observed in button fixation technique as compared to vaginopexy technique. The duration of postoperative treatment was less in vaginopexy technique as compared to the button fixation technique. Overall, the vaginopexy was significantly better and excellent then the button fixation technique.
Keywords: Half circled “U” shaped needle; Button fixation technique; Vaginopexy